Effect of Different Educational Methods on Oral Hygiene Status of 7-13-Year-Old Hearing-Impaired Children in Tehran - N Sahaf; M Ghasemi; N Askarizadeh (Islamic Azad University, 2021)
Background and Aim: Hearing impairment is a leading challenge in the education of deaf children. Compared to normal children, hearing-impaired (HI) children have poor oral health due to a lack of communication skills and effective health educations. This leads us to search for a proper method to educate these children. The present study aimed to assess the effect of different educational methods on the oral health of 7-13-year-old HI children in Tehran. Material and Methods: In this clinical trial, 76 HI children, aged 7 to 13 years, were selected from elementary schools of deaf children in Tehran according to the entry criteria. They were examined, and the baseline plaque and gingival scores were recorded using the Silness and Loe plaque index (PI) and the Loe and Silness gingival index (GI). The children were randomly divided into two groups; one group was educated using a dental model, and the other group watched a guided training video. Oral health education was reinforced two weeks later. Reexamination was carried out 4 months later. Data were statistically analyzed using t-test with SPSS version 20.0.  Results: There was a significant reduction in plaque and gingival scores in both groups after health education (P<0.05). The highest reduction in plaque and gingival scores was seen in the dental model group. Conclusion: In a comparison between the two educational methods (dental model and video), training using a dental model is more efficacious in improving the oral health of HI children. Continuous school-based oral health education programs for HI children need to be considered.